Upaya Guru Bimbingan dan Konseling Dalam Meningkatkan Kegiatan Belajar Peserta Didik - Zarniati, Zarniati; Alizamar, Alizamar; Zikra, Zikra (Konselor, 2014)
This was is descriptiveresearch which is aimed at revealing the efforts done by the guidance and counselingteacher to improve the students’ activity in SMP Negeri Kota Padang. In collecting the data, the researcher used guestionnaires which were distributed to the sample 30 students. Based on the result of data analisys, it was revealed that the efforts done by the teacher in improving the students’ activity was in very good category. The percentage of the activity was 82,77%.